2020
DOI: 10.3390/ijms21239264
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: Emerging Diagnostic and Therapeutic Targets in Cutaneous Diseases

Abstract: Skin is the largest human organ and is continuously exposed to various exogenous and endogenous trigger factors affecting body homeostasis. A number of mechanisms, including genetic, inflammatory and autoimmune ones, have been implicated in the pathogenesis of cutaneous diseases. Recently, there has been considerable interest in the role that extracellular vesicles, particularly exosomes, play in human diseases, through their modulation of multiple signaling pathways. Exosomes are nano-sized vesicles secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 194 publications
0
24
0
1
Order By: Relevance
“…Exosomes are 40–150 nm small extracellular vesicles, which are involved in the regulation of cellular microenvironment. They carry cargo such as RNA (including mRNAs, microRNAs, and non-coding RNAs), DNA, protein, and lipids to facilitate communications between cancer cells ( Jeppesen et al, 2019 ; Khan et al, 2020 ). During the past several years, there have been many reports on miRNAs in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are 40–150 nm small extracellular vesicles, which are involved in the regulation of cellular microenvironment. They carry cargo such as RNA (including mRNAs, microRNAs, and non-coding RNAs), DNA, protein, and lipids to facilitate communications between cancer cells ( Jeppesen et al, 2019 ; Khan et al, 2020 ). During the past several years, there have been many reports on miRNAs in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…6,55 More specifically, keratinocytes which are the main components of the epidermis, can also release EVs and regulate skin homeostasis, including immune responses and wound healing. 11,[62][63][64] Emerging evidence also suggests that miRNAs participate in the progression of immune diseases. 59,65 Notably, EVs contain a large amount of miRNA cargo and were proven to be immunologically active and their levels were associated with disease activity in patients suffering from inflammatory skin diseases.…”
Section: Inflammatory Skin Disordersmentioning
confidence: 99%
“…110 Briefly, cancer cells actively release EVs which convey bioinformation (such as miRNA and proteins) to neighboring cancer cells or benign cells, thus mediating protumor processes such as angiogenesis, immune regulation and modification of tissue microenvironments, contributing to the development and metastasis of cancer. 11,58,110 Several studies have also shown that various miRNAs and proteins involved in cell growth, development, migration, metastasis and apoptosis are highly expressed in EVs released from melanoma cells. [117][118][119][120] In addition to melanoma, Tumor-derived exosomes (TDEs) in Head and Neck Squamous Cell Carcinoma (HNSCC) are also involved in cancer initiation, invasion and progression, therapeutic application and resistance to treatment.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, EVs are crucial in terms of initiating and propagating the inflammation in psoriasis. Emerging evidence highlights the immunologic role of IL-17, a pro-inflammatory cytokine secreted from T helper 17 cells (T h 17 cells) [13]. Levels of IL-17α in EVs of dermal dendritic cells (DCs) were correlated with the severity of the disease symptoms [14].…”
Section: Role Of Extracellular Vesicles In Skin Diseasesmentioning
confidence: 99%